Carbon Accounting in the Oil and Gas Industry: Regulatory Obligations or Corporate Legitimacy Strategy? - Siti Bunayyah Fakhirah; Rina Tjandrakirana (Escalate : Economics and Business Journal, 2026)
Climate change and the increase in carbon emissions are prompting the oil and gas industry to adopt carbon accounting practices. Nevertheless, in Indonesia, this initiative lacks robust regulatory backing, leading to doubts about whether it is motivated by legal requirements or the pursuit of legitimacy. This research is focused on examining how regulations and stakeholder pressure influence this practice, using a qualitative literature review of studies sourced from Scopus, SINTA, and Google Scholar from 2021-2026. The findings indicate that the desire for legitimacy plays a greater role in driving carbon accounting than adherence to regulations. Additionally, it has a dual effect, imposing immediate costs and performance challenges while also offering long-term advantages such as enhanced reputation, increased investor confidence, and sustainability. Thus, carbon accounting functions both as a strategy for gaining legitimacy and as an investment in sustainability.